Motivational Factors to Adopt Social Media Technology in Small Medium Enterprises - Setyowati, Nuning; Irianto, Heru (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2020)
Social media technology has become part of the community needs, not only as a means to socialize but also to support business operations. In the MEA era, the demands of the market expansion of business networks become mandatory for employers, including for SMEs. This study aim to analyze the motivational factors of SMEs to use social media technologies to support their business activities. This study used survey technique and analysis of Structural Equation Modeling  with  PLS analysis tools. The results showed that perceived enjoyment have positive effect on the perceived ease of use of social media technology, Perceived ease of use have positive effect toward the perceived usefulness, perceived enjoyment and perceived ease of use have positive effect to attitudes towards the use of social media technology, Perceived usefulness and attitude towards the use of social media technology have positive effect toward the intention of using social media technology.